2012
DOI: 10.1111/ans.12001
|View full text |Cite
|
Sign up to set email alerts
|

Dedicated emergency theatres improve service delivery and surgeons' job satisfaction

Abstract: Background: There are well-described benefits to separating emergency and elective surgery. Geelong Hospital lacked the resources to implement a separate acute surgical unit, but instituted daily dedicated emergency general surgery operating sessions, managed by an on-site consultant. This study aims to assess the impact of this on service delivery and surgeons' job satisfaction. Methods: From 1 February 2011, daily half-day operating lists were allocated for general surgical emergencies. Patients treated on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(48 citation statements)
references
References 7 publications
0
48
0
Order By: Relevance
“…It has been shown that even without a designated ‘acute surgery only’ emergency theatre, a short consult‐to‐surgery time as well as more in‐hours operating can still be achieved. Effective communication between various surgical teams and with the duty anaesthetist ensures cases were performed in order of clinical urgency …”
Section: Review Of Gsa 12‐point Planmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that even without a designated ‘acute surgery only’ emergency theatre, a short consult‐to‐surgery time as well as more in‐hours operating can still be achieved. Effective communication between various surgical teams and with the duty anaesthetist ensures cases were performed in order of clinical urgency …”
Section: Review Of Gsa 12‐point Planmentioning
confidence: 99%
“…Effective communication between various surgical teams and with the duty anaesthetist ensures cases were performed in order of clinical urgency. 60,61 The service must be valued (recognized, rewarded, resourced and renumerated)…”
Section: Egs Should Be Consultant Ledmentioning
confidence: 99%
“…These are each limited to a single hospital or city. Increased satisfaction was observed in 13 Australian EGS surgeons assessed before and after ASU implementation . Similarly, a Canadian study enrolled 12 surgeons working in either the ASU of one hospital or the traditional structure of another, with higher satisfaction observed in the former group .…”
Section: Discussionmentioning
confidence: 96%
“…The ASU model is frequently vaunted to increase EGS staff satisfaction. Although supported by multiple post‐hoc questionnaires of registrars, surgeons or patients, only two comparative studies exist . These are each limited to a single hospital or city.…”
Section: Discussionmentioning
confidence: 99%
“…At the RAH, patients with acute general surgical problems are admitted by the acute surgical unit (ASU). ASUs have been propagated throughout many tertiary Australian hospitals in the 21st century as a superior way to manage the emergency caseload with improved outcomes for clinicians and patients . The first to be developed was at Prince of Wales Hospital in 2005 .…”
Section: Introductionmentioning
confidence: 99%